Evaluation of germplasm, fungicides and biocontrol agents against anthracnose (Colletotrichum gloeosporioides) in mango (Mangifera indica) nursery - Singh, Harinder; Arora, Anita; Kaur, Sumanjit; Kaur, Kirandeep (The Indian Journal of Agricultural Sciences, 2020)
Mango anthracnose caused by Colletotrichum gloeosporioides Penz. is economically important disease of mango (Mangifera indica L.). The experiments were conducted to evaluate the germplasm and efficacy of fungicides, biocontrol agents against anthracnose in mango nursery at Punjab Agricultural University, Ludhiana, University Seed Farm, Ludhiana and M S Randhawa Fruit Research Station, Gangian, Hoshiarpur during 2017-18. Twenty five mango cultivars were screened both under laboratory conditions by using detached leaf method and under field conditions. All the cultivars had shown susceptible reaction under laboratory and field conditions with highly susceptible reaction of Malika under laboratory conditions. The fungicides (carbendazim, thiophanate methyl, azoxystrobin, propiconazole, difenoconazole, copper oxychloride, mancozeb) and two biocontrol agents (Trichoderma harzianum and Pseudomonas fluorescens) were evaluated in vitro through poisoned food technique and dual culture technique, respectively. Azoxystrobin and propiconazole were found to be highly effective in inhibiting the mycelial growth (100%) of C. gloeosporioides at 50 μg/ml and 100 μg/ml and at 100 μg/ml, respectively. All the fungicides and biocontrol agents, tested in vitro were also evaluated under field conditions for management of mango anthracnose. Azoxystrobin and propiconazole were significantly effective in reducing per cent disease index and providing disease control at Ladhowal, Ludhiana and Gangian, Hoshiarpur.